Archaeological surveys in the Lurin River Basin 1970-1993 - Bueno Mendoza, Alberto (2012)
Archaeological studies in the Lurin River Basin provide insight territorial geomorphology, his constant ecosystem and physiography and climate of the valley in general. In parallel perspective recognized also technically social settlement patterns recognizing that the “settlement pattern” is a theoretical and methodological model that studies urban concentrations occupying the countryside. Besides using eco-cultural determinations study environmental data by applying the theory of systems that can identify the interconnection and cultural relations of the archaeological sites in regional study